Prospek Pengelolaan Lingkungan Dalam Upaya Pengendalian Serangga Kesehatan - hasan boesri (ASPIRATOR - Journal of Vector-borne Disease Studies, 2010)
Environment is an important media for the life of all creatures in this world. It always changes accordingly based onto the nature change and human act. Its control mosquito has been done for the purpose of reducing the transmission’s source, by establishing PanamaCanal on 1904-1907, Polentine Marsh Project in Italy on 1930, Water Irrigation program for Tennese Valley Authority (TVA) in USA on 1935-1945 and Aedes aegypti control in each water content for housesholds needs in Brazil, on 1930. By that time (1939-1944),DDT was starting to spread out in Italy. Those methods were used to control Pediculus sp. This factor created ups and downs on the methods application